NON-INVASIVE BIOPHYSICAL EVALUATION OF MICROCIRCULATION USING THERMAL IMAGING IN YOUNG ADULTS (Western European Journal of Medicine and Medical Science, 2025)
Microcirculation plays a fundamental role in tissue metabolism, thermoregulation, and vascular homeostasis. Early functional disturbances in microvascular regulation often remain clinically undetected, particularly in young adults, despite their potential contribution to long-term cardiovascular and metabolic risk. From a biophysical perspective, alterations in microcirculatory function are closely linked to changes in heat transfer and surface temperature distribution. This study investigates the use of thermal imaging as a non-invasive biophysical method for evaluating microcirculatory function in young adults. Skin surface temperature patterns were analyzed to assess peripheral perfusion and microvascular regulatory behavior under resting conditions. Emphasis was placed on spatial and functional thermal characteristics rather than absolute temperature values. The analysis revealed heterogeneous thermal patterns indicative of early microcirculatory imbalance, even in individuals without apparent clinical symptoms. The findings suggest that thermal imaging provides sensitive biophysical markers of functional microcirculatory alterations. Application of this approach may enhance early detection of microvascular vulnerability and support preventive assessment strategies in young adult populations